Migraine Prophylaxis, Ischemic Depolarizations, and Stroke Outcomes in Mice. Issue 1 (January 2015) - Eikermann-Haerter, Katharina; Lee, Jeong Hyun; Yalcin, Nilufer; Yu, Esther S.; Daneshmand, Ali; Wei, Ying; Zheng, Yi; Can, Anil; Sengul, Buse; Ferrari, Michel D.; van den Maagdenberg, Arn M.J.M.; Ayata, Cenk
Abstract : Background and Purpose—: Migraine with aura is an established stroke risk factor, and excitatory mechanisms such as spreading depression (SD) are implicated in the pathogenesis of both migraine and stroke. Spontaneous SD waves originate within the peri-infarct tissue and exacerbate the metabolic mismatch during focal cerebral ischemia. Genetically enhanced SD susceptibility facilitates anoxic depolarizations and peri-infarct SDs and accelerates infarct growth, suggesting that susceptibility to SD is a critical determinant of vulnerability to ischemic injury. Because chronic treatment with migraine prophylactic drugs suppresses SD susceptibility, we tested whether migraine prophylaxis can also suppress ischemic depolarizations and improve stroke outcome. Methods—: We measured the cortical susceptibility to SD and ischemic depolarizations, and determined tissue and neurological outcomes after middle cerebral artery occlusion in wild-type and familial hemiplegic migraine type 1 knock-in mice treated with vehicle, topiramate or lamotrigine daily for 7 weeks or as a single dose shortly before testing. Results—: Chronic treatment with topiramate or lamotrigine reduced the susceptibility to KCl-induced or electric stimulation-induced SDs as well as ischemic depolarizations in both wild-type and familial hemiplegic migraine type 1 mutant mice. Consequently, both tissue and neurological outcomes were improved. Notably, treatment with a single dose of either drug was ineffective. Conclusions—: These data underscore the importance of hyperexcitability as a mechanism for increased stroke risk in migraineurs, and suggest that migraine prophylaxis may not only prevent migraine attacks but also protect migraineurs against ischemic injury.